The effects of opposition and gender on knee kinematics and ground reaction force during landing from volleyball block jumps - Hughes, G.; Watkins, J.; Owen, N. (Research Quarterly for Exercise and Sport, 2010)
The aim of this study was to examine the effect of opposition and gender on knee kinematics and ground reaction force during landing from a volleyball block jump. Six female and six male university volleyball players performed two landing tasks: (a) an unopposed and (b) an opposed volleyball block jump and landing. A 12-camera motion analysis system (120 Hz) was used to record knee kinematics, and a force platform (600 Hz) was used to record ground reaction force during landing. The results showed a significant effect for level of opposition in peak normalized ground reaction force (p = .04), knee flexion at ground contact (p = .003), maximum knee flexion (p = .001), and knee flexion range of motion (p = .003). There was a significant effect for gender in maximum knee flexion (p = .01), knee flexion range of motion (p = .001), maximum knee valgus angle (p = .001), and knee valgus range of motion (p = .001). The changes in landing biomechanics as a result of opposition suggest future research on landing mechanics should examine opposed exercises, because opposition may significantly alter neuromuscular responses.